Effect of antiprotozoal drugs on the proliferation of the bivalve parasite Perkinsus olseni - Elandalloussi, Laurence M. (2014)
The protozoan parasite Perkinsus olseni causes severe losses among Ruditapes decussatus clams. The development of an in vitro culture of this parasite together with the use of a proliferation assay has provided the opportunity to screen for drug sensitivity of this parasite. Xenobiotics known for their antimalarial and antiprotozoal properties were tested against P. olseni. Only four of these drugs, namely cycloheximide, pyrimethamine, deferoxamine (DFO) and 2,2-bipyridyl (BIP), showed in vitro inhibitory effect on the parasite proliferation. Two in vivo experiments were designed to determine the effect of iron chelators on reducing P. olseni infection in clams. For this purpose, naturally infected clams from the Ria Formosa, Portugal, were exposed to DFO and BIP at various concentrations. In the first experiment, hemolymph samples were taken from each clam before and after treatment to determine the infection intensity and in the second experiment, clams were randomly distributed in groups of five and the parasite burden in treated and untreated groups was determined at the end of the experiment on the whole clam wet tissues. Only DFO was found to be effective in reducing in vivo P. olseni infections. In addition, acute toxicity of DFO and BIP has been determined and no mortality of Perkinsus-free clams was observed.